The questioning as poetic expression of Neruda´s uncertainty (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Even though Neruda sometimes pointed out his “metaphysical works” todifferentiate them from his contingent poetry, the existential background of his work is evident, especially during the last stage of his lyrical creation. His questions related Neruda´s essential concern about the concrete and unique existence of mankind, chiefly that of mankind and its history as well as that of the self and its individual conditioning threatened by death. This paper highlights the constant question-like attitude. This type of attitude is the one that the poet employs to face the outside world and reality and his own, which turns into an interpretative key to his work. From Neruda´s beginning, his poetry intended to be all-embracing, questioning himself a gamut of aspects pertaining to reality. This does not imply necessarily a discourse dealing with a cognitive or philosophical function, but rather a metaphorical one, which focuses on “what reality is all about”.
Keywords: Pablo Neruda; Chilean Literature; poetry; Nobel Prize; uncertainty u